Penerapan dan Evaluasi Promosi Gizi Pada Anak Sekolah di SD dan SMP Kota Yogyakarta - Budiningsari, Dwi; Hartriyanti, Yayuk; Hardiyanti, Marina; Witaningrum, Riani; Annisa Putie, Sridanti; Ryveka, Aurellia; Guna Risma, Aini; Nur Andani, Anisya (Universitas Dinamika, 2026)
Nutrition programs to overcome adolescent’s nutrition problems using a school-based approach are considered the most effective nutrition program strategy. As an effort to support nutrition programs at the school level, SEAMEO RECFON, together with experts in the field of health nutrition and strategic partners developed the